2014
DOI: 10.2355/isijinternational.54.511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micro-porosities on Fatigue Behavior in Aluminum Die Castings by 3D X-ray Tomography Inspection

Abstract: In this investigation, porosities in fatigue specimens obtained from practical ADC12 high pressure die castings were detected and reconstructed with high resolution X-ray computed tomography technology. Three dimensional (3D) characterizations of the porosities were analyzed. The high cycle fatigue tests were carried out at five stress amplitudes on seven groups of the specimens with different porosity contents. The Weibull analysis suggested less scatter of the fatigue life at larger stress condition. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Then, a dimensionless quantity related to the diameter of pore is introduced to the damage evolution equations to reflect the effect of stress concentration induced by a pore. It is found that the calculated fatigue lives are in accordance with the experimental results [7]. materials, can be represented by the deterioration ratio of the stiffness of representative volume element (RVE): …”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Then, a dimensionless quantity related to the diameter of pore is introduced to the damage evolution equations to reflect the effect of stress concentration induced by a pore. It is found that the calculated fatigue lives are in accordance with the experimental results [7]. materials, can be represented by the deterioration ratio of the stiffness of representative volume element (RVE): …”
Section: Introductionsupporting
confidence: 68%
“…The fractured surfaces of all specimens were observed with a scanning electron microscope (SEM). Part of the results [7] are shown in Table 2. …”
Section: Fatigue Life Prediction Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In steel manufacturing conditions, many methods have been developed to improve the quality of steel and achieve automatic inspection. In this introduction, we briefly mention the various inspection techniques that have been developed for steel manufacturing environments, which include ultrasonic detection methods for stainless steel spot welds 2) and ductile iron, 3) quality monitoring using voltage signals for small-scale resistance spot welding, 4) 3D X-ray tomography inspection for fatigue in aluminum die castings, 5) and optical inspection techniques for slabs, 6,7) steel bar, 8,9) billets, 10) and silicon steel. 11) Although the several studies mentioned above have achieved good performance and can effectively detect their respective defects, it is difficult to apply them directly to defect detection in thick plate surfaces because each of these methods is optimized for a…”
Section: Introductionmentioning
confidence: 99%
“…Though initially CT scans were used mainly for industrial, engineering, and medical purposes (McColl et al, 2006;Kuwazuru et al, 2008;Nicoletto et al, 2010Nicoletto et al, , 2012Wan et al, 2014) X-ray micro computed tomography from micro-CT scanners and X-ray synchrotron imaging has become increasingly popular as a diagnostic and analytical tool for palaeontologists, archaeologists, and other Natural Science disciplines as it is entirely nondestructive and provides detailed 3D images of the structure of whole animals or plants, the remains of fossils buried in amber, rock, or hard substrate, and the interior of fossil bones and teeth (Tafforeau et al, 2006;Kearney et al, 2005;Lak et al, 2008;Sutton, 2008;Jasinoski et al, 2010;Jasinoski and Chinsamy, 2012;Huttenlocker et al, 2013;Holloway et al, 2014;Dollion et al, 2015;Wichura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%